Toripalimab plus chemotherapy in the treatment of metastatic triple-negative breast cancer: a cost-effectiveness analysis - Hongfu Cai; Lisheng Huang; Zhiwei Zheng (Frontiers Media S.A., 2024)
ObjectiveThis study focuses on assessing the cost-effectiveness of incorporating toripalimab alongside chemotherapy for the treatment of patients diagnosed with metastatic triple-negative breast cancer from the perspective of the Chinese healthcare system.MethodsA partitioned survival model was constructed to simulate the costs and health outcomes over the lifetime of patients with mTNBC. Clinical data regarding overall survival, progression-free survival, and treatment-related adverse events were derived from the TORCHLIGHT clinical trials. Incremental cost-effectiveness ratio (ICER) were calculated based on the gains in quality-adjusted life-year (QALY). The willingness-to-pay (WTP) threshold was defined as $39,855.79 per QALY. Additionally, sensitivity analyses were conducted to examine the robustness of the model.ResultsThe total cost incurred by the group receiving toripalimab was $38,040.62, while the placebo plus chemotherapy was $26,102.07. The utilization of the toripalimab regimen resulted in an increase of 0.74 QALYs and an incremental cost of $11,938.55 compared to the placebo plus chemotherapy group. The ICER was $16,133.18/QALY, indicating that toripalimab plus chemotherapy is a cost-effective strategy according to the WTP threshold. Sensitivity analyses confirmed the robustness of the results.ConclusionThis study suggests that the addition of toripalimab to chemotherapy for the treatment of mTNBC is a cost-effective strategy. The findings provide valuable evidence to guide decision-making regarding treatment selection for patients with mTNBC in China.